Pemberdayaan Home Industri melalui Pengelolaan Arus Kas dan Pelatihan Promosi Digital pada Masyarakat Kelurahan Sekip Pekanbaru - Ibrahim, Mariyati; Sulistyani, Andri; Augustin, Jeneva; Muhammad, Fahmi; Prambudi, Yogi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The community empowerment program through capacity building for home-industry entrepreneurs is an important step in supporting local economic growth, especially amid increasingly competitive business conditions. This community service activity was carried out in Sekip Subdistrict, Pekanbaru, with a primary focus on cash-flow management and digital promotion training for home-based business owners. The problems identified in the field included limited understanding among entrepreneurs regarding making it difficult for them and plan long-term budgets. In addition, low digital literacy resulted in many home-industry products being unable to reach wider markets. Through this program, participants received training on simple cash-flow management using daily recording methods, preparation of monthly financial reports, and strategies for separating business and personal finances. Practical mentoring was conducted to ensure that participants could apply these techniques independently. In the aspect of digital promotion, participants were trained to utilize various platforms such as Facebook, Instagram, WhatsApp Business, and online marketplaces. The training materials included creating engaging content, basic product photography techniques using simple devices, and strategies for maintaining consistency in digital marketing.Evaluation results showed a significant improvement in participants’ understanding of financial management and digital-based promotion techniques. In addition, several participants succeeded in increasing sales after applying the digital promotion techniques taught. Overall, the program contributed positively to strengthening the business capacity of the community in Sekip Subdistrict and opened opportunities for sustainable income growth. For program sustainability, continued mentoring and collaboration with local government are needed so that the impact can be further optimized.